Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445137
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Interaction: An Embodied Metaphor Inspired Approach to Designing for Meditation

Abstract: Meditation is a mind-body practice with considerable wellbeing benefits which can take different forms. Novices usually start with focused attention meditation that supports regulation of attention towards an inward focus or internal bodily sensations and away from external stimuli or distractors. Most meditation technologies employ metaphorical mappings of meditative states to visual or soundscape representations to support awareness of mind wandering and attention regulation, although the rationale for such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…The Body mapping probe has been particularly useful in supporting access to these interoceptive experiences, although some participants found it difficult to engage with. This is not entirely surprising, as such probe draws from interoceptive awareness which requires time to develop [13,27] . Nevertheless, the body mapping probe could benefit from additional instructions to better scaffold participants' engagement with it.…”
Section: Affordance Of Sensory Probes Formentioning
confidence: 99%
“…The Body mapping probe has been particularly useful in supporting access to these interoceptive experiences, although some participants found it difficult to engage with. This is not entirely surprising, as such probe draws from interoceptive awareness which requires time to develop [13,27] . Nevertheless, the body mapping probe could benefit from additional instructions to better scaffold participants' engagement with it.…”
Section: Affordance Of Sensory Probes Formentioning
confidence: 99%
“…Staying focused in the moment and not becoming distracted is an essential but difficult skill that technology could support [5,12]. Researchers have explored various technologies and their resulting embodiments to lower the difficulty of learning and engaging in mindfulness meditation as well as increase the effectiveness of meditation for users.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, we designed the speakers making up the "body" of the wandering VA to be placed close, even intimately near, to the user's body to see how it would affect the guided meditation experience. In addition, Daudén Roquet and Sas [12] and Ståhl et al [29] explored how the location of warmth affected breathing and attention control. They found that temperature feedback aided breathing control; this inspired us to imagine how other senses, hearing and tactility, affected meditation.…”
Section: Related Workmentioning
confidence: 99%
“…The project 'The Sonic Cradle' is another example [50] that feeds back biodata to the user. Also, the work of Daudén Roquet & Sas [11] focuses on design for bringing attention to the body through their conceptual design WarmMind. These projects focus on using various sensory feedback to practice mindfulness, see also [8].…”
Section: Mindfulness In Hcimentioning
confidence: 99%